2019
DOI: 10.1002/nop2.394
|View full text |Cite
|
Sign up to set email alerts
|

Health status and self‐management in patients with inflammatory arthritis—A five‐year follow‐up study after nurse‐led patient education

Abstract: AimThe aim of this study was to investigate changes in patients' self‐management and health status five years after nurse‐led patient education.DesignA longitudinal study.MethodsWe collected self‐reported data on physical function, pain, tiredness, disease activity, psychological status, patient activation and self‐efficacy from a sample of Norwegian‐speaking adults with inflammatory arthritis that had participated in a randomised controlled study investigating the effects of nurse‐led patient education. Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…The participants experienced a reduction in symptoms, such as less pain, fatigue, and emotional distress, which indicates the potential of selfmanagement approaches in targeting the negative impact of chronic illnesses. This resonates with ndings from other trials that have found that self-management interventions and nurse-led patient education have led to signi cant improvements in symptoms such as fatigue, pain, sleep problems, anxiety and depression along with coping skills, self-e cacy, illness perception and QoL, with effects lasting over time (22,(42)(43)(44)(45). Regarding absenteeism, only a few were in paid work, but the attitude expressed during the interviews was that the participants prioritised work and tried to not be absent despite the challenges caused by their IA.…”
Section: Discussionsupporting
confidence: 64%
“…The participants experienced a reduction in symptoms, such as less pain, fatigue, and emotional distress, which indicates the potential of selfmanagement approaches in targeting the negative impact of chronic illnesses. This resonates with ndings from other trials that have found that self-management interventions and nurse-led patient education have led to signi cant improvements in symptoms such as fatigue, pain, sleep problems, anxiety and depression along with coping skills, self-e cacy, illness perception and QoL, with effects lasting over time (22,(42)(43)(44)(45). Regarding absenteeism, only a few were in paid work, but the attitude expressed during the interviews was that the participants prioritised work and tried to not be absent despite the challenges caused by their IA.…”
Section: Discussionsupporting
confidence: 64%
“… 12 (86%) 4 Gronning et al 42 2016 Norway Qualitative study within the published randomized control trial University hospital Adult RA patients last included in the randomized control trial Nurse-led hospital-based patient education program 26 (intervention 15, control 11) PAM of intervention group 73, of control group 70 A small group of which had RA The experiences from the Patients in the nurse-led patient education program were in concordance with the pathway of self-efficacy and patient activation, which many patient education programs are based on 10 (71%) 5 Joplin et al 40 2014 Australia Cohort Mid-North Coast Arthritis Clinic (MNCAC), a community-based rheumatology practice in Coffs Harbour 18 patients with RA Joint ultrasound 60.0 (±15.5) at baseline Very small sample size, PAM was reported as a continuous variable and was not computed to levels PAM-13 scores did not change during the The study, with levels of activation at T1, T2, and T3 of 60.0 (±15.5), 55.7 (±12.0) and 57.8 (±14.8) (p = 0.21), respectively. 7 (50%) 6–8 Gronning et al 41 , 49 follow-up study after 5 years 50 2012 2013, 2019 Norway Randomized control trial University hospital 141 of which a group of patients had RA 101 follow-up 63 of which had RA Nurse-led hospital-based patient education program Reports of the first study include intervention PAM 65.7 (±13.3), control PAM 65.6 (±16.4) Not all patients had RA, the exact number of RA patients was not mentioned, PAM was reported as a continuous variable and was not computed to levels Reported results at 4 and 12 months, then 5 years follow-up. A significant improvement of PAM scores among women with intervention at 12 months, mean change 4.2 (0.0, 8.3, p = 0.048).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that patient education can contribute to changing behavior and improving compliance with the prescribed preventive and therapeutic measures [ 9 , 10 ]. These educational interventions include clinical decision support, education, patient-involvement strategies, telephone and email support follow-up [ 11 , 12 ], mobile health technology [ 13 ], and nurse-led educational intervention [ 14 ], significantly improving knowledge, drug adherence, and quality of life in patients with CVD.…”
Section: Introductionmentioning
confidence: 99%